Justification of vacuum prophylaxis as part of the penile rehabilitation in patients after nerve-sparing radical prostatectomy - A. E. Osadchinskiy; I. S. Pavlov; S. V. Kotov (Вестник урологии, 2021)
Introduction. In healthy men, a significant increase in pO2 in the cavernous tissue occurs during episodes of nocturnal erections. This process ensures sufficient oxygenation and high-pressure substances such as prostaglandin-E1 and nitric oxide. These substances suppress the expression of transforming growth factor β1, thereby preventing collagen synthesis and the development of cavernous fibrosis. In patients undergoing nerve-sparing radical prostatectomy, nocturnal erections are absent, hypoxia inhibits the production of PGE-i, and neuropraxia inhibits NO. Thus, cavernous fibrosis develops through the production of pro-apoptotic and profibrotic factors, resulting in persistent erectile dysfunction. The importance of a vacuum in penile rehabilitation for the prevention of penile cavernous hypoxia is not fully understood. This is due to the deficiency of data on the gas composition of cavernous blood when a vacuum-induced erection is achieved.Purpose of the study. To investigate the cavernous blood at the time of vacuum-induced erection, to analyze the obtained results with the International Index of Erectile Function score and with the values of penile hemodynamics.Materials and methods. The study included i5 patients with prostate cancer and preserved sexual function. The average age of all men was 57.87 ±4.36 years. All patients underwent a preoperative comprehensive assessment of erectile function: International Index of Erectile Function questionnaire, dynamic duplex penile ultrasound. Immediately prior to the surgery, penile blood was collected at the time of achieving a vacuum-induced erection. The gas composition and oxygenation were assessed using the values of the partial oxygen pressure, carbon dioxide and saturation in accordance with the approved standards to differentiate arterial and venous blood. Statistical data processing was carried out using the PASW Statistics 22 software (IBM SPSS, IBM Corp., Chicago, IL, USA)Results. All patients were divided into 3 groups depending on the gas composition and oxygen level of the cavernous blood. Group I included 4 (26.6%) patients with a predominance of arterial blood, group II — 4 patients (26.6%) with venous blood and group III — 7 patients (46.6%) with a mixed composition of cavernous blood. The average International Index of Erectile Function score in group I was 23.5 [2i.0; 25.0], in group II — 22.0 [2i.0; 24.0] and in group III — 24.0 [i9.0; 25.0]. Peak systolic velocity (cm/s) in group I was 40.i [35.i; 45.2], in group II — 35.9 [29.5; 50.2], in group III — 32.5 [32.5; 34.4]. End-diastolic velocity (cm/s) in group I was 2.52 [0.55; i0.5], in group II — 8.3 [2.9; i0.8], in group III — 7.5 [7.5; 9.0]. Resistive index in group I was 0.87 [0.77; 0.98], in group II — 0.75 [0.63; 0.94], in group III — 0.75 [0.73; 0.75].Conclusions. Vacuum prophylaxis may be the method of choice for penile rehabilitation in patients after nerve-sparing radical prostateectomy, especially in the early postoperative period during neuropraxia. The use of vacuum devices should be prescribed to patients with preserved veno-occlusive mechanism, which should be confirmed by dynamic duplex penile ultrasound.